THE INFLUENCE OF BRAND PERSONALITY ON CONSUMER PURCHASE INTENTION OF NIKE SPORTSWEAR PRODUCTS IN MANADO - Mamangkey, Christheo M.; Lapian, Joyce S.L.H.V. Lapian; Tumbuan, Willem J. F. A (Universitas Sam Ratulangi, 2018)
Nike is the world's largest supplier and manufacturer of athletic shoes, apparel and other sports equipment. The company employed about 74,400 people worldwide in 2017, and their global revenue generated more than 34 billion U.S. dollars. In the current era business has been growing very rapidly. This study was examining the influence of brand personality on consumer purchase intention of Nike Sportswear Products. There are five core dimensions of brand personalities: sincerity, excitement, competence, sophistication and ruggedness. The research conducted by using multiple regression analysis and collecting the data from questionnaire. The sample in this study is taken by 100 respondents of people living in Manado. The result shows that brand personality of sincerity, competence, and ruggedness has significantly influence on consumer purchase intention of Nike Sportswear Products. It was found that competence is the variable that most has significantly influence on consumer purchase intention of Nike Sportswear Products than any other brand personalities. This means that the consumers trust in the brand, consider it as a successful brand. Therefore, Nike just need to keep maintain their competence because this is one of the influencing factors of their brand personality that will keep the consumer want to buy their products.Keywords: brand personality, sincerity, excitement, competence, sophistication, ruggedness, and purchase intention